Equity of financial protection for health in high-income countries: scoping review protocol - Shehzad Ali; Beate Sander; Michael Law; Sara Allin; Edward C Xie; Diego Proaño (BMJ Open)
Introduction Financial protection (FP) is a central function of health systems to enhance access to essential care and improve health equity. We aim to characterise evidence on the distribution of FP in high-income countries as well as how equity of FP is conceptualised and measured in these settings. Findings from this review can advance methodological and conceptual knowledge about equity in FP, guide the evaluation of health systems and inform policy on eliminating inequitable barriers to care to achieve universal health coverage.Methods and analysis We will undertake a scoping review following guidance from Colquhoun et al and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews. We will search four academic databases covering health sciences and economic literature as well as four grey literature sources for relevant publications. Screening for eligibility will be performed independently by two reviewers after calibration of screening criteria. Data will be charted using a standardised form and summarised by thematic analysis.Ethics and dissemination Institutional research ethics review was not required; however, research ethics will be considered iteratively throughout the research process. Research findings will be disseminated to scientific and policy meetings, summarised for lay audiences and submitted for publication in a peer-reviewed journal.